2020
DOI: 10.3389/fcell.2020.586541
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Mucosa Mesenchymal Stem Cells Alleviate Cerebral Ischemia/Reperfusion Injury Via Golgi Apparatus Secretory Pathway Ca2+ -ATPase Isoform1

Abstract: Olfactory mucosa mesenchymal stem cells (OM-MSCs) have exhibited their effectiveness in central nervous system diseases and provided an appealing candidate for the treatment of ischemic stroke. Previous evidence have shown that Golgi apparatus (GA) secretory pathway Ca 2+ -ATPase isoform1 (SPCA1) was a potential therapeutic target for ischemic stroke. In this study, we explored the neuroprotective mechanism of OM-MSCs and its effect on the expression and function of SPCA1 during cerebral ischemia/reperfusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…Although we suggested that hypoxic OM-MSCs inhibited microglial pyroptosis in ICH, the specific mechanism of the inflammatory response of microglia regulated by hypoxic OM-MSCs after ICH injury is still unclear. Previously, we demonstrated that OM-MSCs exerts neuroprotective effects on cerebral ischemia/reperfusion injury (47,48,50). We also revealed that hypoxia-preconditioned OM-MSCs inhibit pyroptotic death of microglial cells by activating the hypoxia inducible factor-1α (HIF-1α) in vitro model of ischemic stroke (49).…”
Section: Effects Of Mscs On Microglial Pyroptosis Post-ichmentioning
confidence: 97%
See 1 more Smart Citation
“…Although we suggested that hypoxic OM-MSCs inhibited microglial pyroptosis in ICH, the specific mechanism of the inflammatory response of microglia regulated by hypoxic OM-MSCs after ICH injury is still unclear. Previously, we demonstrated that OM-MSCs exerts neuroprotective effects on cerebral ischemia/reperfusion injury (47,48,50). We also revealed that hypoxia-preconditioned OM-MSCs inhibit pyroptotic death of microglial cells by activating the hypoxia inducible factor-1α (HIF-1α) in vitro model of ischemic stroke (49).…”
Section: Effects Of Mscs On Microglial Pyroptosis Post-ichmentioning
confidence: 97%
“…Olfactory mucosa MSCs (OM-MSCs) localized in the nasal lamina propria have recently been recognized as an ideal source of MSCs, as they are easily accessible and situated for autologous transplantation (46). Previously, we demonstrated that OM-MSCs exerts neuroprotective effects in ischemic stroke (47,48). We also revealed that hypoxia-preconditioned OM-MSCs inhibited microglial pyroptosis in an in vitro model (49) and affirmed that hypoxic preconditioning enhanced the therapeutic efficacy of OM-MSCs in an in vivo model (50).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2012a) have found that adipose-derived mesenchymal stem cells (ADMSCs) attenuated cerebral ischemia-reperfusion injury through suppressing iNOS. Another two interesting findings indicated that olfactory mucosa mesenchymal stem cells (OM-MSCs) exert neuroprotective effects by rescuing the function of mitochondria and Golgi apparatus and enhancing antioxidation via upregulation of UBIAD1 and SPCA1 (He et al, 2020;Liu et al, 2020b). Moreover, that MSCs modified with diverse molecules exhibited antioxidative stress effects on ischemic stroke models have also been reported, such as C-C motif chemokine receptor 2 (CCR-2), brain-derived neurotrophic factor (BDNF), and circRNA-Akap7 (Lu et al, 2016;Huang et al, 2018b;Xu et al, 2020).…”
Section: Mscs Inhibit the Production Of Ros And Rnsmentioning
confidence: 99%
“…Olfactory mucosa MSCs (OM-MSCs), located in the nasal lamina propria, are an attractive source of stem cells as they are relatively easy to obtain and ideally suited for autologous transplantation [ 10 ]. Previously, we demonstrated that OM-MSCs exert neuroprotective effects in cerebral ischemia/reperfusion injury [ 11 , 12 ], but no study has explored the neuroprotective effects of OM-MSC therapy in ICH.…”
Section: Introductionmentioning
confidence: 99%